Integrating SWOT and Business Model Canvas for MSMEs Development - Bayu Wahyudi; Nidya Wisudawati; Adellia Gustianda (Universitas Atma Jaya Yogyakarta, 2026)
MSMEs Pempek Koyek is a business engaged in the production of traditional Palembang food, facing several challenges, including a decline in sales due to the COVID-19 pandemic, limited promotional activities, a lack of an online store, and a less strategic location. This study aims to identify and analyze the internal and external factors that affect the business, and to formulate effective strategies for growth. A mixed-methods approach was adopted, using SWOT analysis and the Business Model Canvas (BMC) framework. Data collection included observations, interviews with owners, customers, and stakeholders, and surveys distributed to 122 respondents identified using Slovin's formula. The SWOT analysis revealed that the company is positioned in Quadrant I, suggesting the adoption of an aggressive Strength-Opportunity (S-O) strategy. Key strategies include using social media and e-marketplaces to promote high-quality products, forming strategic partnerships with the hospitality industry, diversifying product offerings, enhancing social media engagement, and optimizing customer service with faster delivery. The BMC approach focused on enhancing key activities, including raw material sourcing, product innovation, and digital marketing. The results of this study provide valuable insights into the strategic development of MSMEs, particularly in the food sector, by combining internal strengths with external opportunities. The findings contribute to the growing body of knowledge on MSME development and offer practical strategies for business sustainability in a competitive market environment.